EFEKTIFITAS KAMPANYE ANTI PENYALAHGUNAAN NARKOBA TERHADAP PENGETAHUAN DAN SIKAP REMAJA AKAN BAHAYA PENYALAHGUNAAN NARKOBA (Studi Terhadap Remaja di Kelurahan Sukaraja Kecamatan Teluk Betung Selatan, Kota Bandar Lampung) - Primantari, Visi Arum; Kahono, Gunawan Budi (SOCIOLOGIE, 2013)
This research aimed at knowing and explaining the effectiveness of the campaign anti abuse of illegal drugs towards knowledge and the attitude the adolescent would the abuse danger of illegal drugs. The research method that was used was descriptive that had a purpose systematically the fact or the characteristics of the certain population or the certain field factually. Results of the research showed that the campaign anti abuse of effective illegal drugs towards knowledge and the attitude the adolescent would the abuse danger of the Medias illegal drugs that were used in the campaign to be able to take the form of knowledge about the abuse danger of illegal drugs or the outside media (the example: the banner, the poster, leaflat, etc.).Keywords: Campaign, abuse of illegal drugs, awareness, teens